Affective functioning among early adolescents at high and low familial risk for depression and their mothers: A focus on individual and transactional processes across contexts - McMakin, Dana L. (2011)
This study aimed to characterize affective functioning in families of youth at high familial risk for depression, with particular attention to features of affective functioning that appear to be critical to adaptive functioning but have been underrepresented in prior research including: positive and negative affect across multiple contexts, individual and transactional processes, and affective flexibility. Interactions among early adolescents (ages 9-14) and their mothers were coded for affective behaviors across both positive and negative contexts. Primary analyses compared never-depressed youth at high (n=44) and low (n=57) familial risk for depression. The high risk group showed a relatively consistent pattern for low positive affect across negative and positive contexts at both the individual and transactional level. In contrast to prior studies focusing on negative affect that did not support disruptions in negative affect, the data from this study suggest variability by context: (i.e. increased negativity in a positive, but not negative, context) and individual vs. transactional processes (e.g., negative escalation). Findings are discussed in concert with attention to affect flexibility, contextual and transactional factors.